2018
DOI: 10.3390/ma11071131
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of CaCO3-TiO2 Composite Particles and Their Pigment Properties

Abstract: CaCO3-TiO2 composite particles were prepared with calcium carbonate (CaCO3) and TiO2 in stirred mill according the wet grinding method. The pigment properties, morphology, and structure of CaCO3-TiO2 composite particles and the interaction behaviors between CaCO3 and TiO2 particles were explored. In the CaCO3-TiO2 composite particles, TiO2 is uniformly coated on the surface of CaCO3 and the firm combination between CaCO3 and TiO2 particles is induced by the dehydration reaction of surface hydroxyl groups. CaCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…There is a small number of uncovered CaCO 3 and a large number of coating TiO 2 on the surface of CaCO 3 -TiO 2 [18]. For CaCO 3 , its outermost surfaces are coated by TiO 2 and there are only a small number of unsaturated Ca 2+ and CO 3 2− on its surface.…”
Section: Surface Organic Modification Model Of Caco 3 -Tiomentioning
confidence: 99%
“…There is a small number of uncovered CaCO 3 and a large number of coating TiO 2 on the surface of CaCO 3 -TiO 2 [18]. For CaCO 3 , its outermost surfaces are coated by TiO 2 and there are only a small number of unsaturated Ca 2+ and CO 3 2− on its surface.…”
Section: Surface Organic Modification Model Of Caco 3 -Tiomentioning
confidence: 99%
“…Titanium dioxide is a multifunctional material [ 9 ], highly employed in the food (chewing gum with mint flavor, dairy products) and pharmaceutical (sunscreens and toothpaste) industries [ 10 , 11 ]. However, most of the TiO 2 uses, including antibacterial activity, are usually UV-irradiation dependent [ 1 , 2 ], in particular for TiO 2 in the anatase phase (active under UV rays at a wavelength of 385 nm or shorter), which is a limiting factor for their potential applications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the infrared spectrum of the CaCO 3 –TiO 2 composite photocatalyst, the absorption peak at 1636 cm −1 of TiO 2 disappeared, and the absorption peak of CaCO 3 ranging from 3300 to 3500 cm −1 was weakened. It has been suggested that CaCO 3 and TiO 2 form a firm chemical combination through their surface hydroxyl groups [24].…”
Section: Resultsmentioning
confidence: 99%